2011
DOI: 10.1007/s10562-011-0610-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Mesoporosity Generation in ZSM-5 and Zeolite Beta on Catalytic Performance During n-Hexane Isomerization

Abstract: Catalytic performance of Pt impregnated parent and desilicated nano-crystalline zeolites, ZSM-5 and Beta for n-hexane isomerization was studied. Difference in channel systems of the zeolites and absence/presence of mesopores therein were found to be reflected in product distributions. ZSM-5 was desilicated by NaOH and zeolite Beta with tetramethylammonium hydroxide (TMAOH.) Desilication was found to afford comparable catalytic performance to that of the parent counterpart at reaction temperature lower by 25°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
(47 reference statements)
2
17
0
Order By: Relevance
“…Song et al [21] studied the effect of the desilication treatment on ZSM-5, and observed an enhancement in the yield of dibranched isomers due to the formation of mesopores. Modhera et al [22] also studied the catalytic performance of Pt impregnated desilicated ZSM-5 and Beta zeolites for n-hexane hydroisomerization, reporting modifications in Pt location that were correlated to a reduced catalyst deactivation by sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [21] studied the effect of the desilication treatment on ZSM-5, and observed an enhancement in the yield of dibranched isomers due to the formation of mesopores. Modhera et al [22] also studied the catalytic performance of Pt impregnated desilicated ZSM-5 and Beta zeolites for n-hexane hydroisomerization, reporting modifications in Pt location that were correlated to a reduced catalyst deactivation by sintering.…”
Section: Introductionmentioning
confidence: 99%
“…From our earlier experiences with hierarchical zeolite Beta for isomerization of n-hexane, we deduced the following operating conditions to afford the highest isomer yields: catalyst mass 1 g, n-hexane flow rate 6 mL/h, H 2 /hydrocarbon 2 mol/mol, pressure 1 atm, temperature 350 °C, and reaction in continuous down flow reactor [2]. The present work is an extension of our previous efforts to increase the catalyst life and enhance the isomer selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Among the probable candidates, keeping hydrothermal stability of the catalyst in mind, zeolites Beta has remained the catalyst of choice. Readers are referred to relatively recent works [1,2] for introduction to paraffin isomerization and review articles by Valavarasu and Sairam [3], and Akhmedov et al [4] for details and comprehensive intricacies of various commercial processes. Now, when the molecular size of product increases as a result of the reaction, it is worth expecting that (a) smaller crystal size, preferably in nanometer size affording smaller diffusion length and enhanced external surface area and (b) generation of mesoporosity in zeolites crystals would be beneficial for the reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter catalysts are particularly advantageous as they are less corrosive and less prone to deactivation by the contaminants (i.e. water, sulfur) present in the feed [20,21]. Nevertheless, Pt-zeolites catalysts present some disadvantages such as high operating temperatures, high hydrogen pressure and lower acidity which, in the end, leads to lower selectivity to branched molecules [22][23][24].…”
Section: Introductionmentioning
confidence: 99%